1996
DOI: 10.1152/ajpheart.1996.271.3.h1139
|View full text |Cite
|
Sign up to set email alerts
|

Relation between baroreflex sensitivity and carotid artery elasticity in healthy humans

Abstract: We investigated whether physiological variability in arterial baroreflex sensitivity (BRS) was related to differences in carotid elastic behavior among 19 young healthy subjects (age 18-26 yr). The diameter of the carotid artery (D) and its change during the arterial pulse (delta D) were monitored by a phase-locked echotracking device (UT-4 Hokanson), and pulse pressure (delta P) was measured in the brachial artery by sphygmomanometry. Distensibility coefficient (DC) for the common carotid artery was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
71
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 0 publications
3
71
0
3
Order By: Relevance
“…Previous investigations have demonstrated that BRS is significantly related to carotid artery distensibility. A positive association between the elastic properties of the carotid artery and BRS has been reported in healthy volunteers, 25 pregnant women, 26 hypertensive subjects, 27 and nondiabetic patients with carotid artery stenosis. 28 However, in this study we did not observe any correlation between BRS and common carotid artery wall distensibility in T2DM patients with at least 2 additional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous investigations have demonstrated that BRS is significantly related to carotid artery distensibility. A positive association between the elastic properties of the carotid artery and BRS has been reported in healthy volunteers, 25 pregnant women, 26 hypertensive subjects, 27 and nondiabetic patients with carotid artery stenosis. 28 However, in this study we did not observe any correlation between BRS and common carotid artery wall distensibility in T2DM patients with at least 2 additional cardiovascular risk factors.…”
Section: Discussionmentioning
confidence: 90%
“…In the comparative nondiabetic group with similar degree of arterial stiffening as evidence by equally elevated PWV and reduced carotid distensibility, a positive but weak correlation was observed between carotid distensibility and BRS, confirming previous observations in the nondiabetic group of subjects. [25][26][27][28] There are several aspects of the study that deserve clarification to properly interpret the data. First, spontaneous baroreflex sensitivity estimation using the alpha index and the sequence techniques may have a different meaning compared with the traditional phenylephrine method.…”
Section: Discussionmentioning
confidence: 99%
“…17,28 Even in young healthy subjects, decreased BRS is associated with decreased carotid artery distensibility. 29 Arterial distensibility is decreased in borderline as well as in established essential hypertension. 30 Various metabolic and lifestyle factors affect arterial properties and BRS.…”
Section: Discussionmentioning
confidence: 99%
“…12 A relation between BRS and carotid distensibility has been shown in healthy subjects and in hypertensive patients. [13][14][15] With advancing age, both BRS and carotid compliance were found to decrease, and the reduction in BRS was explained in part by stiffening of the arterial wall. 7 It is not known, however, how changes in large-artery compliance influence cardiovagal autonomic function during the childhood years.…”
mentioning
confidence: 99%